Peningkatan Pemasaran Pentingnya Legalitas Lengkap Dan Higienitas Produk Krupuk Pada Usaha Mikro Kecil Menengah - Hakkun Elmunsyah; Sujito; Anik Nur Handayani; Arya Kusumawardana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This community service is located in Mulyoagung Village, Dau District, Malang Regency. The problem faced by partners is the lack of a guarantee of business legality. The next problem is product packaging and labels that are less attractive and do not meet standards, which make it difficult to market products. Solutions that can be proposed with training and assistance to obtain a business license or business legality certificate are in the form of business identification numbers (NIB), home industry food production certificates (SPP-IRT), labels and brands, and product halal guarantees. There is training and assistance in making product packaging and labels, considering that packaging is a very important factor for maintaining quality and attracting customers to buy products when they are marketed. In addition, training and assistance for entrepreneurs in using information technology to market products to a wider market online and offline.